Mobile healthcare applications development on the Android phone - Tsoi, Hung Pan (2014)
Wireless Body Sensor Network (WBSN) is a research area focusing on wearable sensor nodes that are placed on human’s body in order to create a sensor network. By utilizing the data gathered from the sensor nodes that are attached to the body, human’s critical body vital signs can be monitored. In other words, the implementation of WBSN technology is very essential in healthcare, personal physical wellness, professional sports training, rehabilitation, and military.